Functional Astrocyte Heterogeneity and Implications for Their Role in Shaping Neurotransmission - Xin, Wendy; Bonci, Antonello (Frontiers in Cellular Neuroscience, 2018)
In recent years, the role of astrocytes in shaping neuronal signaling has come to the forefront of neuroscience research. The development of genetic tools that enable targeted manipulation of astrocytes has revealed a wealth of mechanisms by which they can alter the synaptic strength and intrinsic excitability of neurons in behaviorally relevant ways. In parallel, several studies have demonstrated significant variability in the gene expression and physiology of astrocytes within and between brain regions. Thus, to form an accurate understanding of how astrocytes contribute to neuronal transmission, we must take into consideration the diversity that exists in their intrinsic properties. In this review, we will summarize recent findings on astrocyte heterogeneity and discuss the implications for their interactions with neurons and their effects on neuronal transmission.